The Legal Study of Land Redistribution Policy as Land Reform Object: State Administrative Law Perspective : Kajian Yuridis atas Kebijakan Redistribusi Tanah Objek Landreform: Perspektif Hukum Administrasi Negara - Rukmi Widowati, Aisyah; Insan Kamil, Azahery (Mendapo: Journal of Administrative Law, 2025)
The land redistribution policy under land reform is a government effort to achieve equitable land ownership in the Unitary State of the Republic of Indonesia, as well as to improve the welfare of the Indonesian people. In practice, this policy often faces various legal and administrative challenges that can hinder its effectiveness. This study aims to analyze the mechanisms of administrative law in implementing the land redistribution policy under land reform, identify legal and administrative challenges encountered, and evaluate legal protections for beneficiaries in facing disputes or third-party claims. The method used in this research is a normative juridical approach with qualitative analysis techniques. The findings of this article indicate that the administrative law mechanisms in land redistribution still require improvement, particularly in inter-agency coordination and procedural transparency. Legal challenges include unsynchronized regulations, inadequate oversight, and budget limitations, while administrative obstacles relate to complex bureaucracy. Additionally, legal protections for beneficiaries remain suboptimal due to weak legal certainty regarding ownership status and potential conflicts with third parties. The conclusion of this article is that administrative procedure simplification and regulatory strengthening are necessary to ensure the effective implementation of the land redistribution policy. The recommendations provided in this article include enhancing coordination among relevant agencies, reforming the agrarian administration system, and providing stronger legal protection for beneficiaries to reduce potential disputes. This article is expected to serve as a reference in the development of land redistribution policies in the Unitary State of the Republic of Indonesia.